2013
DOI: 10.1017/s0954422413000139
|View full text |Cite
|
Sign up to set email alerts
|

The impact of milk proteins and peptides on blood pressure and vascular function: a review of evidence from human intervention studies

Abstract: CVD are the leading cause of death worldwide. Hypertension, a major controllable risk factor of CVD, is intimately associated with vascular dysfunction, a defect which is also now recognised to be a major, modifiable risk factor for the development of CVD. The purpose of the present review was to critically evaluate the evidence for the effects of milk proteins and their associated peptides on blood pressure (BP) and vascular dysfunction. After a detailed literature search, the number of human trials evaluatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 87 publications
2
64
0
4
Order By: Relevance
“…Another mechanism in which dairy products may reduce blood pressure is through milk proteins (4). Bioactive lactotripeptides are hypothesized to lower blood pressure by inhibition of angiotensin-converting enzyme and opioid-like activities (4,27). A reciprocal relation between dairy intake and healthier dietary pattern has been shown in our study as well as in other studies (6,7,10) and suggests that the association between dairy intake and risk of hypertension could be confounded by generally healthier lifestyle and eating habits.…”
Section: Discussionsupporting
confidence: 76%
“…Another mechanism in which dairy products may reduce blood pressure is through milk proteins (4). Bioactive lactotripeptides are hypothesized to lower blood pressure by inhibition of angiotensin-converting enzyme and opioid-like activities (4,27). A reciprocal relation between dairy intake and healthier dietary pattern has been shown in our study as well as in other studies (6,7,10) and suggests that the association between dairy intake and risk of hypertension could be confounded by generally healthier lifestyle and eating habits.…”
Section: Discussionsupporting
confidence: 76%
“…Mariotti et al failed to report any significant effects of casein, whey or α-lactalbumin enriched whey protein on digital volume pulse (a measure of arterial stiffness) (57) (Table 2). Intriguingly, BP-lowering effects of milk proteins were not associated with changes in vascular function in the reviewed RCT (13) which is confirmed by emerging evidence on the relationship between BP and arterial stiffness. This suggests that the interaction between BP and arterial stiffness may be bi-directional (58,59) via complex interactions between different pathways such as inflammatory (60,61) , hormonal (e.g.…”
Section: Short-term Studies On Vascular Functionsupporting
confidence: 65%
“…During our systematic literature search (13) we found that there were very few studies investigating the BP-lowering effects of other casein-derived peptides in human subjects (23)(24)(25)(26)(27) . Furthermore these studies were limited, used different types of peptides and were often uncontrolled with poor methodological and study design.…”
Section: Long-term Studies On Blood Pressurementioning
confidence: 99%
“…Milk is a complex food that contains several potential bioactive compounds; therefore, it remains to be confirmed which constituents may be responsible for the beneficial effect. Previous studies have linked milk-protein consumption with reduced BP (5); however, there has been an imbalance in the literature, because most attention has focused on the casein-derived lactotripeptides or other milk-protein hydrolysates (6) with a clear evidence gap on the effects of intact milk-protein isolates on BP (7). Milk proteins in liquid milk exist in intact forms, and evidence from robust randomized controlled trials (RCTs) would provide valuable information on the potential mechanism by which milk may affect BP.…”
Section: Introductionmentioning
confidence: 99%